Gravitoelectromagnetism and Gravitomagnetic Clock Effect - Chakravorti, B. K.; Faruque, S. B. (Journal of Scientific Research, 2022)
We present a new and elegant method of derivation of the gravitomagnetic clock effect using gravitational Lorentz force, which appears in gravitoelectromagnetism. The result is precisely the same as that of general relativity in the Kerr field.